Handbook of research on strategic management for current energy investments - Yüksel, Serhat; Dinçer, Hasan (IGI Global, 2021)
Energy has a wide range of uses within a country, includin socially and economically. Providing everything from warmth and light to raw materials for industrial production, energy is an essential need for countries. Due to the importance of energy for countries, energy policies are extremely vital, and energy needs to be affordable, eco-friendly, and continuous so countries can provide for their people and continue to develop industrially. Without the availability of energy that is cheap and continuous, the effectiveness in the energy supply process will be reduced, and society will experience difficulties in having its daily energy needs met. The Handbook of Research on Strategic Management for Current Energy Investments analyzes current trends in energy production and use and identifies energy investment strategies in order to support affordable and available energy for all. Chapters within the book cover technological developments that contribute to the reduction of price in energy production as well as renewable energy sources that provide continuity in energy production but do not emit carbon into the atmosphere. This book highlights topics that cover environmental pollution, energy pricing, economic growth, carbon dioxide emission, and energy management. It is ideal for engineers, technicians, managers, researchers, academicians, policymakers, government officials, and students in related fields.
Keywords: Strategic Management; Handbook; Handbook of Research